"Where Is the Time?": Time Poverty and Women's Urban Mobility Narratives in Kochi, India - Fathima Zehba M. P.; Lakshmi Priya Rajendran; Mohammed Firoz C. (Urban Planning)
Time poverty disproportionately affects urban women due to the societal expectations of balancing their work and gender roles. In urban environments, women’s time use is significantly influenced by their daily mobility experiences. Despite a wealth of existing research on time use and mobility, mostly in developed countries, understanding gendered dimensions of mobility and time poverty in cities of developing nations remains unexplored. Using Tiznado Aitken et al.’s (2024) integrated time use framework, the study explores how necessary, committed, contracted, and travel time collectively shape the daily routines of low-income women workers in Kochi City, India. The method involves qualitative analysis of in-depth interviews conducted during December 2022–January 2023. Interview analysis highlights entrenched gender roles disproportionately burdening women with unpaid domestic and caregiving responsibilities, leading to severe time poverty among low-income working women. The study also identifies how time poverty is exacerbated by travel constraints and access to transport services. This study substantially strengthens the literature on time poverty and gendered time use, emphasising the necessity for institutional reforms to elevate the quality of life for urban women workers. The findings presented hold implications for urban planning, transportation policy, and social equity initiatives aimed at enhancing accessibility and inclusivity within cities of the Global South.